Dampak Pademi Covid-19 Terhadap Implementasi Kebijakan Kampus Merdeka (Study Di Universitas Samawa ) - Iskandar, Syaifuddin; Asmini, Asmini; Fitriyani, Ika; Sumbawati, Novi Kadewi (Jurnal Literasi dan Pembelajaran Indonesia, 2022)
The Impact of the COVID-19 Pandemic on the Implementation of the Independent Campus Policy (Study at Samawa University), This study aims to determine the Impact of the COMID-19 Pandemic on the Implementation of the Independent Campus Policy. This type of research uses a qualitative research type, with qualitative data types while the data source is primary data and Secondary Data, sampling technique for informants using snowball sampling technique: those who are considered sufficient to be able to provide opinions and statements that do not change More specifically, the number of selected informants is eight people who are considered very related to interested parties in the implementation The independent campus policy consists of the Chancellor, the Dean of the Head of Lecturer Study Program, the Head of LPPM, the Head of LPMU, the Head of BAAK and the Head of BAUK, while the Data Collection Techniques used in this study are Interview Observation and Documentation. Alisa Duta Qualitative with the constant comparative method or Triangulation by checking the validity of the data used is Triangulation and based on the results of Data Analysis and Discussion, the conclusions of the research on the Impact of the COMID-19 Pandemic on the Implementation of the Independent Campus Policy (Study at Samawa University) which includes 1 Changing the Satker PTN into a BH PTN 2. Simplification of Higher Education Accreditation 1 Opening New Study Programs, 4. Two Semester Off-Campus Activities, 5. Student Exchange, 6. Internship or Work Practice. Teaching Assistantship in Education & Research Unit or Rist. 9 Humanitarian Projects 10 Entrepreneurial Activities 11 Independent Studies/Projects 12 Building Villages or Thematic Real Work Lectures (KKNI) Students 13. Studying Systems, Seminars and Working in Higher Education using Information Technology Online through Zoom Meetings, 14. Learning by Using Information Technology Online through E-Learning 15 Working Using Information Technology Online with Work From Home Shows Positive Impacts and Negative Impacts, namely as follows: Positive Impacts as follows Easier and Efficient because it is carried out Online, Online and Virtual Entrepreneurship Students have a great opportunity in help provide Jasah and open an Online Business, IT Mastery is important, Learning with E-learning can be anytime and anywhere. Learning and working online/school from home and Work From Home are variants for Discipline. Negative Impacts are as follows: All programs are not implemented effectively / not optimally because they are carried out online, during and Viktual and constrained by the provision of internet access, network signal disturbances and limited quotas, we are still not familiar with WFH then Accreditation Implementation is difficult to negotiate directly and there are special conditions that must be met. Being a Teaching Assistant in the Education Unit is constrained because all BDR schools and all activities are constrained by the Health Protocol. Entrepreneurship Students need to choose the entrepreneurial sector ha ha rustepar because people's purchasing power is decreasing.